Ildikó Asztalos-Morell: Emancipation's Dead-end Roads? Studies in the Formation and Development of the Hungarian Model for Agricultural and Gender (1956-1989) (Uppsala: Acta Universitas Upsaliensis, 1999) (Szociológiai Szemle, 2024)
-